2011
DOI: 10.1016/s0973-6883(11)60111-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Asymptomatic Hepatitis C Virus Infection in Bangladesh

Abstract: Objectives: There are paucity of information about prevalence and risk factor of hepatitis C virus (HCV) in Bangladesh. Methods: Blood was collected from 1018 randomly selected subjects from a semi-urban area of Bangladesh. Anti-HCVs were checked in the blood twice using a third-generation commercial kit. The data of the questionnaires were analyzed to find possible risk factors. Results: Nine of the 1018 subjects (88%) were tested positive for anti-HCV. The HCV-positive subjects were >28 years old. Major risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…61 Data from Bangladesh on HCV prevalence is sparse, but is reported to be low (0·84%). 62 Prevalence is as high as 40% in people who inject drugs with unknown HIV status and 60·7% in those with HIV co-infection; therefore, the burden of HCV is highest in people who inject drugs. 63 Most people who do not inject drugs but are infected with HCV have a history of any injection (treatment by non-qualified village doctors), sharing blades in barber shop, or of circumcision by traditional practitioners.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Data from Bangladesh on HCV prevalence is sparse, but is reported to be low (0·84%). 62 Prevalence is as high as 40% in people who inject drugs with unknown HIV status and 60·7% in those with HIV co-infection; therefore, the burden of HCV is highest in people who inject drugs. 63 Most people who do not inject drugs but are infected with HCV have a history of any injection (treatment by non-qualified village doctors), sharing blades in barber shop, or of circumcision by traditional practitioners.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…There have been substantial advances in research on liver diseases in Bangladesh and several epidemiological studies have been published in the past two decades. [56][57][58][59][60][61][62]149,150,[152][153][154][155][156][218][219][220]223,[406][407][408] Still, baseline data on incidence, prevalence, risk factors, natural history, and the changing epidemiology of various causes of liver diseases need to be generated. Studies are needed to develop cheap, accessible, point-of-care testing for HBV and HCV, and on preventive measures and new drug treatments for NAFLD.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…It is estimated that Bangladesh harbors about 8 million chronic hepatitis B virus (HBV) and chronic hepatitis C virus (HCV)-infected people. 2 3 Also, there is frequent outbreak of viral acute hepatitis those are caused by hepatitis A virus (HAV) and hepatitis E virus (HEV). Also, the numbers of patients with noncommunicable disease like nonalcoholic fatty liver diseases (NAFLDs) are on increasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…The included 15 studies with a total sample size of 60 496 reported the prevalence of hepatitis B in Bangladesh and the characteristics of all studies are presented in Table 1. All the included articles [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] were cross-sectional studies and conducted throughout the period ranging from 1995 to 2017. The smallest sample size was 130 [14] and the largest sample size was 43 213 [26].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%